Language and infant mortality in a large canadian province - Auger, Nathalie; Bilodeau-Bertrand, M.; Costopoulos, A. (Public Health, 2016)
Objectives Infant mortality in minority populations of Canada is poorly understood, despite evidence of ethnic inequality in other countries. We studied infant mortality in different linguistic groups of Quebec, and assessed how language and deprivation impacted rates over time. Study design Population-level study of vital statistics data for 1,985,287 live births and 10,283 infant deaths reported in Quebec from 1989 through 2012. Methods We computed infant mortality rates for French, English, and foreign languages according to level of material deprivation. Using Kitagawa's method, we evaluated the impact of changes in mortality rates, and population distribution of language groups, on infant mortality in the province. Results Infant mortality declined from 6.05 to 4.61 per 1000 between 1989–1994 and 2007–2012. Most of the decline was driven by Francophones who contributed 1.39 fewer deaths per 1000 births over time, and Anglophones of wealthy and middle socio-economic status who contributed 0.13 fewer deaths per 1000 births. The foreign language population and poor Anglophones contributed more births over time, including 0.08 and 0.02 more deaths per 1000 births, respectively. Mortality decreased for Francophones and Anglophones in each level of deprivation. Rates were lower for foreign languages, but increased over time, especially for the poor. Conclusions Infant mortality rates decreased for Francophones and Anglophones in Quebec, but increased for foreign languages. Poor Anglophones and individuals of foreign languages contributed more births over time, and slowed the decrease in infant mortality. Language may be useful for identifying inequality in infant mortality in multicultural nations.

Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)